Oxidação de monóxido de carbono sobre catalisadores à base de ferro ou manganês suportados ou trocados em zeólitas H-mordenita ou Ce-mordenita - Sena, Homero Jacinto (Universidade Federal de São Carlos, 2015)
The fluid catalytic cracking (FCC) is one of the most important process in the petroleum refining industry, being responsible for the increase of the yield of the most valuable light hydrocarbons. On the other hand, the FCC process generates big amounts of CO, NOx and SOx emissions. The CO emissions from the most of pollution sources are abatement using noble metal based catalysts. However, the growing demand and scarcity of those metals have caused an increase in the process cost and consequently promoting studies to find alternative catalysts with comparable efficiency and lower in cost. In this respect, the literature had presented interesting results with transitions metal catalysts. Thus, the objective of this work was to prepare exchanged or impregnated Fe or Mn on H-mordenite or Ce-mordenite, which were evaluated between 150 and 550 oC in the CO oxidation with O2, in the presence or absence of interfering compounds (water steam or SO2). The catalysts were characterized by ICP-OES, DRX, DRS-UV-VIS and Mössbauer spectroscopy. The results showed that the preparation procedures of the interchanged or impregnated Fe or Mn catalysts were adequate, and no mordenite crystallinity loss was observed. Contrary to the exchanged Fe or Mn based catalysts, those based on impregnated Fe or Mn oxides showed a important potential as catalysts in the CO oxidation with O2. Then, in the applied operational conditions the Ce-MOR/Fe10, Ce-MOR/Mn5, Ce-MOR/Mn10 e H-MOR/Mn5 catalysts were able to produce an effluent with CO content lower than 500 ppm, which is the allowed limit by the environmental regulations related with FCC units. In the presence of water steam the evaluated Fe or Mn catalysts presented activity loss that was recovered after the elimination of that interfering from the feed. Nevertheless, in the presence of SO2, the tested catalysts showed an irreversible and significantly activity loss.
Keywords: Catálise heterogênea; Mordenita; Troca iônica; Impregnação; Oxidação de monóxido de carbono; Ferro; Manganês; FCC; Mordenite; Ionic exchange; Impregnation; Iron; Manganese; Cerium; CO oxidation; ENGENHARIAS::ENGENHARIA QUIMICA